2019
DOI: 10.1093/ofid/ofz156
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hemoglobin S Trait on Cell Surface Antibody Recognition of Plasmodium falciparum-Infected Erythrocytes in Pregnancy-Associated Malaria

Abstract: Background Sickle cell trait (HbAS) confers partial protection against malaria by reducing the adhesion of Plasmodium falciparum -infected erythrocytes to host receptors, but little is known about its potential protection against placental malaria. Methods Using flow cytometry, we assessed the recognition of HbAA and HbAS VAR2CSA-expressing infected erythrocytes, by plasma from 159 Beninese pregnant women with either HbAA (normal) or HbAS. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…Abnormal display of VAR2CSA on [ 21 , 23 ], and low antibody binding to [ 27 ], the surface of HbAS IEs have been documented previously. Whether this affects the functionality of antibodies elicited in response to these antigens has not been reported.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Abnormal display of VAR2CSA on [ 21 , 23 ], and low antibody binding to [ 27 ], the surface of HbAS IEs have been documented previously. Whether this affects the functionality of antibodies elicited in response to these antigens has not been reported.…”
Section: Resultsmentioning
confidence: 82%
“…Previous studies reported similar IgG levels to VAR2CSA-type PfEMP1 proteins [ 27 ] and prevalence of P falciparum -IEs in the placenta [ 29 ] in HbAS and HbAA pregnant women, suggesting that both groups are equally exposed to VAR2CSA antigen, despite the protection against severe malaria enjoyed by HbAS individuals. As reported previously [ 27 ], levels of VAR2CSA-specific IgG among the Beninese women studied here did not differ significantly between HbAA and HbAS individuals ( Figure 2A and Supplementary Figure 1A ).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…In our proteomics works, statistical analyses were performed in order to conserve only proteins that were differentially phosphorylated or abundant in all the HbAS samples compared to all HbAA samples. Moreover, our cohort, albeit small, reflects the reality, as the co-carriage of HbS with G6PD deficiency and alpha-thalassemia are frequently found in malaria endemic areas ( Chauvet et al., 2019 ; Okafor et al., 2019 ). It is also important to note here that one of our donors, HbAS 1 , only has sickle cell trait.…”
Section: Discussionmentioning
confidence: 93%